2008
DOI: 10.1128/jvi.01615-08
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Selective Impediment of Neuronal Remodeling upon Borna Disease Virus Infection

Abstract: The neurotropic virus Borna disease virus (BDV) persists in the central nervous systems of a wide variety of vertebrates and causes behavioral disorders. BDV represents an intriguing example of a virus whose persistence in neurons leads to altered brain function in the absence of overt cytolysis and inflammation. The bases of BDV-induced behavioral impairment remain largely unknown. To better characterize the neuronal response to BDV infection, we compared the proteomes of primary cultures of cortical neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…We observed that BDV infection led to a significant decrease of H2B acetylation on K5 and K20 (33% and 26% decreases, respectively) ( Fig. 1A), consistent with our previous proteomics findings (9). In addition, infection also induced a decrease of acetylation on K15 but not on K12.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We observed that BDV infection led to a significant decrease of H2B acetylation on K5 and K20 (33% and 26% decreases, respectively) ( Fig. 1A), consistent with our previous proteomics findings (9). In addition, infection also induced a decrease of acetylation on K15 but not on K12.…”
Section: Resultssupporting
confidence: 80%
“…Based on these findings, it was tempting to hypothesize that BDV may modify the host cell chromatin or interact with factors controlling chromatin dynamics. Moreover, in a previous proteomic analysis performed using primary neuronal culture protein extracts, we observed that acetylation of histone H2B was changed upon infection, suggesting that epigenetic signaling could indeed be affected by BDV (9).…”
mentioning
confidence: 99%
“…Recently, it was revealed that MeCP2 is expressed not only in neurons but also in astrocytes and that MeCP2 deficiency in astrocytes causes several abnormalities, such as in BDNF regulation, cytokine production, and neuronal dendritic induction (13). Interestingly, a recent report using proteomic analysis revealed that BDV infection decreases the expression level of MeCP2 in neuronal cells (27). Although it is tempting to speculate that BDV P influences the function of MeCP2 through interference with its phosphorylation, since the function of MeCP2 appears to be regulated by phosphorylation in the CNS (9,32), the expression levels of IGFBP3 are not significantly different in C6 cells transfected with wild-type P and those infected with a phosphorylation mutant of P, P S26/28A (31; data not shown).…”
Section: Borna Disease Virus (Bdv) Is a Highly Neurotropic Negativestmentioning
confidence: 99%
“…The BDV Hu-H1 strain is one of the first three human strains derived from mentally affected patients (12). These strains have been partially characterized by sequencing (13). The remaining neurons were maintained as a control sample.…”
Section: Primary Culture Of Hippocampal Neurons and Viral Infectionmentioning
confidence: 99%